Medical and Law Graduates and their sleep disorders: Daytime oversleep and Risk Factors - de Souza Neta, Adozina Marques; Fink Santos Neves, João Pedro Declerc; Barreto, Íkaro Daniel de Carvalho; Freitas Trindade, Leda Maria Delmondes (Journal of Health & Biological Sciences, 2018)
Backgroud: The exogenous factors such as family dynamics, psychosocial stress, academic hours and lifestyle can alter the quality of sleep and affect the people’s physical, occupational, cognitive and social functioning. Objectives: evaluate the epidemiological profile, excessive daytime sleepiness, risk factors and the quality of sleep among university students. Method: Cross-sectional study with 701 Medical and Law students from a private Brazilian Northeastern College. The Sociodemographic profile, Pittsburgh Sleep Quality Index and Epworth Sleepiness Scale questionnaires have been applied. The data were submitted to simple and percentage frequency as well as bivariate and multivariate analysis. Significance level: 5%. Results: The sample was with 659 students, 243(37%) of Medicine and 416(63%) of Law. Age group 18-24 years, predominance of females, age group 18-24 years, female 393 (60%); they self-declared being white 282 (42.7%) and brown 303 (45.9%), said they were single 604(92%) and alcohol consumers more than 60%. Poor sleep quality and sleep disturbance were found in 169(70%) medical students and 221(54%) in law ones, being statistically significant (p <0.001) for the medical students. In this comparison, The Law students presented a higher risk (RR 1.34 (1.15-1.56), p <0.001) for disturbance and poor sleep quality. The risk of excessive daytime sleepiness versus drug use represented 71% (RR 1.71, 95% CI 1.18-2.49) for law students. General concerns, studies, anxiety and insomnia were the most frequent risk factors. Conclusion: Risk factors which are part of Medical and Law students’ daily routine affect their sleep quality and increase the risks of excessive daytime sleepiness.